Heat-induced gelation of mixtures of whey protein isolate and sodium caseinate between pH 5.8 and pH 6.6. (December 2016) - Nguyen, Bach T.; Nicolai, Taco; Chassenieux, Christophe; Schmitt, Christophe; Bovetto, Lionel
Abstract: The influence of sodium caseinate (SC) on heat induced gelation of whey protein isolate (WPI) was studied in pure water and in 0.1 M NaCl at pH 5.8, 6.0, 6.3 and 6.6. The critical gel concentration (Cg ) was determined for pure protein solutions and for mixtures containing 40, 60 or 80% SC. Analysis of the aggregates that were formed by the heated mixtures at C < Cg showed that SC did not aggregate, but did influence the aggregation process of WPI. When the fraction of SC in the mixture was less than about 50% it inhibited WPI aggregation, but when it was higher it led to formation of larger aggregates and a reduction of the WPI concentration needed to form a gel. Oscillatory shear measurements were done to study the gelation process and the gel microstructure was investigated with confocal laser scanning microscopy. Graphical abstract: Highlights: Sodium caseinate does not co-aggregate with WPI when heated in mixtures. Low concentrations of caseinate inhibits thermal WPI aggregation and gelation. High concentrations of caseinate favours thermal WPI aggregate growth. Caseinate competes with WPI for calcium ions.